Rol de la inflamación y medición de calprotectina fecal en síndrome de intestino irritable - Gompertz G., Macarena; Montenegro U., Cristián; Covarrubias R., Natalia; Hurtado H., Carmen; Madrid S., Ana María (Revista Hospital Clínico Universidad de Chile, 2012)
Irritable Bowel Syndrome (IBS) is a common gastrointestinal disorder mainly manifested as abdominal pain with correlated changed bowel habits. IBS pathophysiology is still not completely understood; recently, a lot of investigations suggest the role of inflammation and immune activation, most presenting as alteration of mast cells, lymphocytes and cytokines. Several biological markers of intestinal inflammation has been developed, there is not one ideal, but fecal calprotectin has great potential. In this review we will analyze the role of inflammation in IBS and the potential utility of fecal calprotectin.